INTERFACE OF HUMAN RIGHTS, TERRORISM AND COUNTERTERRORISM - Chinmaya Kumar Mohapatra , Sidhartha Das (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
There is global concern about the fight between human rights and terrorism. Considering the various situations, however, the type of terrorism is quite different. Human Rights claims arise where terrorism violates the individual's minimum basic rights. Therefore, the term "human rights" is synonymous with "terrorism." Indian national and foreign militant organisations are actively and threateningly active, damaging local property, killing innocent people. To monitor this hazard, the state has restricted physical resources. On the other hand, the terrorists posed a significant threat to the internal security of the country. Terrorism is an old issue, posing new challenges. It has had a drastic impact on human life and the world economy. It is a plague against humanity. Human rights and terrorism are closely linked. Terrorism is considered to have occurred in many stages in documented history in almost every part of the world since the 9/11 attacks on the World Trade Center in the United States and the 13 December 2001 attacks on the Indian Parliament and the 26 November 2008 attacks in Mumbai. Terrorism has taken on a new dimension and has challenged the very foundations of global civilizationIndia is not unfamiliar to terrorism. It has long been a militant sufferer, whether in the North-East, Punjab, or Jammu & Kashmir. Moreover, over the last half decade terrorism has spread to other parts of the world. The paper addresses the effect that terrorism has on human rights and what its implications are..